Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1111/eve.12084
|View full text |Cite
|
Sign up to set email alerts
|

Abortogenic viruses in horses

Abstract: Summary Viral causes of abortion include equine viral arteritis (EVA) and infection with equine herpesviruses‐1 and ‐4 (EHV‐1 and EHV‐4). Transmission of equine arteritis virus (EAV) occurs through respiratory, venereal or transplacental routes. Horizontal respiratory transmission of EAV results from exposure to infective nasopharyngeal secretions from acutely infected horses. For this transmission to occur, direct and close contact between horses is necessary. Venereal infection is an efficient method of tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 64 publications
0
14
0
Order By: Relevance
“…Indeed, the EHV-8 strains isolated from two aborted foetuses of horses in this study were identified incorrectly as EHV-1 during initial testing, due to cross reactivity of the PCR assay. Viral causes of abortion in horses have only been attributed to EHV-1, and less frequently EHV-4 and equine viral arteritis [ 47 ]. In future, EHV- 8 will need to be included in the differential diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the EHV-8 strains isolated from two aborted foetuses of horses in this study were identified incorrectly as EHV-1 during initial testing, due to cross reactivity of the PCR assay. Viral causes of abortion in horses have only been attributed to EHV-1, and less frequently EHV-4 and equine viral arteritis [ 47 ]. In future, EHV- 8 will need to be included in the differential diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, equine herpesvirus type 2 has an affinity for conjunctival epithelial cells (4). Other viruses can also cause conjunctivitis in horses: Equine Arteriritis Virus (EAV), Equine Influenza Virus (EIV) or less frequently adenoviruses (2,3,6,7). The most common ocular signs include eye discharge (mucous to purulent), redness and conjunctival oedema and photophobia (6).…”
Section: Praca Oryginalnamentioning
confidence: 99%
“…Equine herpesvirus 1 (EHV-1) can cause sporadic or "storms" of abortions worldwide Hong et al, 1993a;Smith et al, 2003;Szeredi et al, 2008;Butt and Carrick, 2010;Bażanów et al, 2014). The virus initially infects the mare via the respiratory tract with a subsequent viremia allowing infection of the endometrial vascular endothelial cells at the base of the microcotyledans (Lunn et al, 2009).…”
Section: Viralmentioning
confidence: 99%
“…Foetuses are usually aborted from mid to late gestation due to an increased susceptibility of the uterine endothelial cells to the virus during this period (Bażanów et al, 2014). Foals may be stillborn after sudden expulsion and are often still within the amniotic sac (Bażanów et al, 2014).…”
Section: Viralmentioning
confidence: 99%
See 1 more Smart Citation